English Literature Students’ Problems in English Writing: A Comprehensive Analysis - Ismail, Dario Rifki; Pranata, Aqil Julyanriko; Jaya, Patria Handung (Journal of Islamic Studies and Education, 2025)
Conveying a written idea in other languages is really a challenge, especially for students. Not only does the challenge come from the grammar of the target language, but the vocabulary also takes a big deal. These things can result in unclear ideas and failure in written communication. This research aims to find out students’ problems in English writing. The data were taken from the writing of English Literature students of Universitas Ahmad Dahlan with samples from three classes. The types of writing were varied starting from essay, formal letter, and topic-based writing. The major finding shows that the students have problems in the subject and verb agreement where they have problems in classifying the subjects and verbs in compound and complex sentences. Besides, the structure of the sentences is sometimes incorrect, especially in forming long phrases. This research is expected to be able to make more students aware of the mistakes and give some clues for the teachers or lecturers related to some problems faced by students in composing a piece of writing.